2001
DOI: 10.1016/s0960-9822(01)00241-x
|View full text |Cite|
|
Sign up to set email alerts
|

A reverse genetic analysis of components of the Toll signaling pathway in Caenorhabditis elegans

Abstract: In C. elegans, tol-1 is important for development and pathogen recognition, as is Toll in Drosophila, but remarkably for the latter rôle, it functions in the context of a behavioral mechanism that keeps worms away from potential danger.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
204
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 377 publications
(209 citation statements)
references
References 71 publications
3
204
1
1
Order By: Relevance
“…Worms are attracted to, or avoid, different bacteria [68,105,106], and it is not yet known whether these behaviors are mediated primarily via a single bacterially produced chemical, or whether a set of chemicals must be recognized as an ensemble to provide a chemical signature for a specific bacterial strain. Similarly, although a major regulator of worm behavior and development is levels of the constitutively produced dauer pheromone [8][9][10][107][108][109], the neurons that respond to pheromone are also not yet defined.…”
Section: Mapping Chemicals To Chemosensory Neuronsmentioning
confidence: 99%
“…Worms are attracted to, or avoid, different bacteria [68,105,106], and it is not yet known whether these behaviors are mediated primarily via a single bacterially produced chemical, or whether a set of chemicals must be recognized as an ensemble to provide a chemical signature for a specific bacterial strain. Similarly, although a major regulator of worm behavior and development is levels of the constitutively produced dauer pheromone [8][9][10][107][108][109], the neurons that respond to pheromone are also not yet defined.…”
Section: Mapping Chemicals To Chemosensory Neuronsmentioning
confidence: 99%
“…In contrast, relatively little is known about innate immunity in the nematode Caenorhabditis elegans. Recent work has shown that C. elegans is killed by a variety of bacterial and fungal pathogens, including Pseudomonas aeruginosa (4)(5)(6)(7)(8)(9)(10)(11)(12). When this experimental host-pathogen system was used, a forward genetic screen for C. elegans mutants exhibiting enhanced susceptibility to P. aeruginosa-mediated killing (Esp phenotype) identified two components of a mitogen-activated protein kinase (MAPK) signaling cascade, the MAPK kinase kinase, NSY-1, and the MAPK kinase, SEK-1, that are required for pathogen resistance (13).…”
mentioning
confidence: 99%
“…These important and diverse functions make NF-B one of the best-studied transcriptional factors in biology (2). Unexpectedly, in Caenorhabditis elegans, the NF-B protein is absent, and similar functional homologues (Toll, Traf, Cactus) are not involved in innate immune response (5). This led to the suggestion that the p38 mitogen-activated protein kinase pathway, which mediates the immune response in C. elegans, is the ancestral signaling pathway of the common ancestor of nematodes, arthropods, and vertebrates, predating the evolution of the NF-B immune signaling pathway (6).…”
mentioning
confidence: 99%